Effect of pretreatment techniques on food waste solubilization and biogas production during thermophilic batch anaerobic digestion - Menon, Ajay (2016)
The purpose of this study was to optimize the alkaline, ultrasonication, and thermal pretreatment in order to enhance the solubilization of food waste (FW) for the production of volatile fatty acids, hydrogen, and methane in thermophilic batch anaerobic digestion. Initially, the effect of pretreatment techniques in the acidogenic phase was studied, and the optimal combinations of different conditions were determined. It was found that each pretreatment technique affected food waste solubilization differently. Alkaline pretreatment increased hydrogen yield in the acidogenic sludge by four times over control. COD solubilization was increased by 47 % when FW pre-heated at 130 °C for 60 min. Ultrasonication at 20 kHz and 45 min reduced processing time to 38 h from the 60–80 h needed in normal operation. Response surface methodology (RSM) was used to optimize a combination of alkaline, ultrasonication, and thermal pretreatment. Optimized conditions were applied to methanogenic single-stage thermophilic AD process, and their impact on biogas production was monitored. Results showed that FW heated at 130 °C for 50 min geminates biogas production compared to control experiment. In conclusion, a short thermal pretreatment regime could significant affect biogas production in single-stage thermophilic AD.